Genome Expression Analyses Revealing the Modulation of the Salmonella Rcs Regulon by the Attenuator IgaA - Mariscotti, Javier F. (American Society for Microbiology (ASM), 2009)
Intracellular growth attenuator A (IgaA) was identified as a Salmonella enterica regulator limiting bacterial growth inside fibroblasts. Genetic evidence further linked IgaA to repression of the RcsCDB regulatory system, which responds to envelope stress. How IgaA attenuates this system is unknown. Here, we present genome expression profiling data of S. enterica serovar Typhimurium igaA mutants grown at high osmolarity and displaying exacerbated Rcs responses. Transcriptome data revealed that IgaA attenuates gene expression changes requiring phosphorylated RcsB (RcsB∼P) activity. Some RcsB-regulated genes, yciGFE and STM1862 (pagO)-STM1863-STM1864, were equally expressed in wild-type and igaA strains, suggesting a maximal expression at low levels of RcsB∼P. Other genes, such as metB, ypeC, ygaC, glnK, glnP, napA, glpA, and nirB, were shown for the first time and by independent methods to be regulated by the RcsCDB system. Interestingly, IgaA-deficient strains with reduced RcsC or RcsD levels exhibited different Rcs responses and distinct virulence properties. spv virulence genes were differentially expressed in most of the analyzed strains. spvA expression required RcsB and IgaA but, unexpectedly, was also impaired upon stimulation of the RcsC→RcsD→RcsB phosphorelay. Overproduction of either RcsB(+) or a nonphosphorylatable RcsB(D56Q) variant in strains displaying low spvA expression unveiled that both dephosphorylated RcsB and RcsB∼P are required for optimal spvA expression. Taken together, our data support a model with IgaA attenuating the RcsCDB system by favoring the switch of RcsB∼P to the dephosphorylated state. This role of IgaA in constantly fine-tuning the RcsB∼P/RcsB ratio may ensure the proper expression of important virulence factors, such as the Spv proteins.